Adverse Pregnancy Outcomes and Cardiovascular Risk Factor Management - Mehta, Puja K. (Semin Perinatol, 2015)
Cardiovascular disease (CVD) is the leading health threat to American women. In addition to established risk factors for hypertension, hyperlipidemia, diabetes, smoking, and obesity, adverse pregnancy outcomes (APOs) including pre-eclampsia, eclampsia, and gestational diabetes are now recognized as factors that increase a woman’s risk for future CVD. CVD risk factor burden is disproportionately higher in those of low socioeconomic status and in ethnic/racial minority women. Since younger women often use their obstetrician/gynecologist as their primary health provider, this is an opportune time to diagnose and treat CVD risk factors early. Embedding preventive care providers such as nurse practitioners or physician assistants within OB/GYN practices can be considered, with referral to family medicine or internist for ongoing risk assessment and management. The American Heart Association (AHA)/American Stroke Association (ASA) stroke prevention guidelines tailored to women recommend that women with a history of pre-eclampsia be evaluated for hypertension and other CVD risk factors within 6 months to 1 year post-partum. Given the burden and impact of CVD on women our society, the entire medical community must work to establish feasible practice and referral patterns for assessment and treatment of CVD risk factors.